Response to a peer telehealth intervention for emergency department patients presenting with opioid use disorder or unintentional overdose: a stratified interrupted time series analysis - Martha Tillson; Huiping Xu; Alan McGuire; Spencer Medcalf; Francesca L. Beaudoin; Dennis P. Watson (Substance Abuse Treatment, Prevention, and Policy)
Abstract Background People in the United States who use opioids frequently use emergency department (ED) services. Some hospitals have begun placing peer recovery support specialists (PRSS) in EDs to support and advocate for patients and provide linkages to services, in an effort to reduce future presentations for opioid-related and other health problems related to substance use. However, evidence supporting the impact of PRSS services on reducing future ED presentations is limited, and even less is known about ED-based PRSS services delivered via telehealth. Methods Using records from a large Indiana-based hospital system, we conducted an interrupted time series (ITS) analysis of ED patients presenting for unintentional opioid overdose or other opioid-related issues. Over a five-year period, 2,542 unique ED visits were included across 12 hospitals. The primary outcome assessed was the impact of PRSS telehealth service implementation (comparing pre- and post-periods) on 30-day all-cause ED revisits. Analyses were also stratified by appropriate demographics. Results There was no significant change in 30-day ED revisits between pre- and post-implementation of the PRSS telehealth program. Results of sex-stratified ITS indicated a significant change for females only, with decreasing log-odds of ED revisits post-program implementation (post-implementation slope OR = 0.911, p = 0.031; slope change OR = 0.874, p = 0.017). Conclusions Although there was no detectable difference in overall ED revisits following program implementation, outcomes of stratified analyses suggested that the program may have been more impactful for females vs. males. Future research should examine the underlying mechanism of the observed sex differences to target behavioral change more effectively for all participants of telehealth PRSS services in ED settings.